Evaluation of orientation and efficiency of schoolchildren nutrition in recreational period - Podrigalo, Leonid; Iermakov, Sergii; Rovnaya, Olga; Yermakova, Tetiana; Cieślicka, Mirosława; Muszkieta, Radosław (Progress in Nutrition, 2020)
Background: determination of antioxidant orientation schoolchildren of nutrition in recreationalperiod and evaluation of its efficiency. Methods: it is studied nutrition of 221 schoolchildren aged 7-15 yearsold at children’s recreational institution. It is used the method of analysis of menu production records withthe subsequent calculation of average daily set of foods, specifying its chemical composition and energy value.The efficiency of nutrition was estimated according to indicators of vitamin and antioxidant statuses. Thedynamics of excretion of vitamins C, B2 and B6 was studied in hour-long portion of urine. The features ofurine bio-chemiluminescence in 9 indicators are estimated. Studies were conducted on 2-3 and 22-23 daysof recreation. Result: it is confirmed the existence of antioxidant direction of nutrition by means of sufficientcontent of total protein, aromatic amino acids, phospholipids, tocopherols, B vitamins, S, Zn. Content ofSe, ascorbic acid in food ration was insufficient. It is determined 16 indicators which are most objectivelycharacterized antioxidant direction of food ration. Conclusion: The nutritional factor influenced positively onvitamin and antioxidant status of organism. The determined correlation dependences between indicators ofbiochemiluminescence and level of vitamins egestion confirmed the efficiency of nutritional factor for influenceon schoolchildren’s health.